PENDAMPINGAN PENDIDIKAN KEWIRAUSAHAAN UNTUK KELOMPOK PKM GURU SEKOLAH DASAR - Arita Marini; Desy Safitri; Ika Lestari; Musril Zahari; Zulela M. S.; Arifin Maksum (Prosiding Seminar Nasional Pengabdian Kepada Masyarakat, 2021)
Abstract The purpose of this international collaboration of community service activity is to provide entrepreneurship education assistance for elementary school teacher groups. The implementation method used in this activity was carried out in a systematic, structured, and directed manner through interactive discussions, demonstrations, simulations, and filling out questionnaires. The learning system used assistance and guidance from partner mentors from Konstanz University of Applied Sciences in Germany, Prof. Dr. Christian von Luebke. After mentoring activities were completed, an evaluation was carried out to measure the effectiveness of the mentoring activities. This international collaboration of community service activity was carried out for 12 elementary school teachers in DKI Jakarta Province on July 12, 2021 for the first session about “entrepreneurship and education”, July 19, 2021 for the second session about “methods and tools for an entrepreneurial mindset”, and July 26 2021 for the third session about “realizing an entrepreneurial mindset” through the zoom platform. Based on the evaluation measurement, teachers' interest in entrepreneurship education reached 86.75% and they will implement entrepreneurship education for elementary school students to improve their creativity and critical thinking. The results of the satisfaction survey assessed from 16 aspects of the assessment of international collaboration of community service activity show that the average satisfaction level of participants was 94%. Abstrak Tujuan kegiatan Pengabdian kepada Masyarakat (PkM) kolaborasi internasional ini adalah untuk melakukan pendampingan Pendidikan Kewirausahaan untuk kelompok PkM guru sekolah dasar. Metode pelaksanaan yang digunakan dalam kegiatan PkM kolaborasi internasional ini dijalankan secara sistematis, terstruktur, dan terarah melalui diskusi interaktif, demonstrasi, simulasi, pengisian angket. Sistem pembelajaran dalam kegiatan PkM internasional ini menggunakan pendampingan dan bimbingan dari mentor mitra dari Konstanz University of Applied Sciences di Jerman, Prof. Dr. Christian von Luebke. Setelah kegiatan pendampingan selesai, dilakukan evaluasi untuk mengukur efektivitas dari kegiatan pendampingan tersebut. Kegiatan PkM kolaborasi internasional ini dilakukan untuk 12 guru SD di Provinsi DKI Jakarta pada 12 Juli 2021 untuk sesi pertama tentang “kewirausahaan dan pendidikan”, 19 Juli 2021 untuk sesi kedua tentang “metode dan alat untuk pola pikir kewirausahaan”, dan 26 Juli 2021 untuk sesi ketiga tentang “mewujudkan pola pikir kewirausahaan” melalui platform zoom. Berdasarkan pengukuran evaluasi, minat guru terhadap pendidikan kewirausahaan mencapai 86,75% dan mereka akan menerapkan pendidikan kewirausahaan bagi siswa sekolah dasar untuk meningkatkan kreativitas dan kemampuan berpikir kritis mereka. Hasil survey kepuasan yang dinilai dari 16 aspek penilaian kegiatan PkM kolaborasi internasional menunjukkan rata-rata tingkat kepuasan peserta kegiatan PkM kolaborasi internasional sebesar 94 %.